Who do we compare ugly people with? Standards of ugliness in the Russian language - Аkosheva, Мarzhan; Rakhimzhanov, Кanat; Temirgazina, Zifa (Slavia Centralis, 2022)
The article explores the standards of human ugliness in the Russian language, expressed in comparisons and metaphors, based on the material of the National Corpus of the Russian Language. Standards are included in the figurative component of the concept "ugliness". The essence of ugliness is defined as a deviation from the norm and stereotype of a person’s appearance. Thematically, the standards of ugliness are combined into groups of zoonyms, Slavic and antique mythonyms and names of literary heroes. The cognitive basis for choosing the standard of ugliness can be the archetype "ours" – "alien", for example, in the group of zoonyms (monkey, marmoset, camel) or in the names of "alien", non-Christian gods (Buddha, Buryat god). The most frequent standard of ugliness is the precedent name of the literary hero – Quasimodo. In our opinion, this is due to the fact that prototypical features of ugliness are embodied in his image: A hump, a limp, a wart on the face. Standards of ugliness are gender-marked – they characterise either male or female ugliness; some of the standards are not gender-marked and characterise both male and female ugliness, depending on the context.
Keywords: concept; ugliness; standards; comparative figure of speech; zoonyms; mythonyms